The deerslayer, or, The first war-path - Cooper, James Fenimore, 1789-1851.; Beard, James Franklin, 1919-1989. (Albany : State University of New York Press, 1987)
Natty Bumppo, a young white hunter brought up in the Delaware Indian tribe, has to defend settlers before returning to the Iroquois who have allowed him parole.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Bumppo, Natty -- (Fictitious character) -- Fiction; Bumppo, Natty -- (Fictitious character); Frontier and pioneer life -- New York (State) -- Fiction; Delaware Indians -- Fiction; Iroquois Indians -- Fiction; United States -- History -- French and Indian War, 1754-1763 -- Fiction; Iroquois -- Romans, nouvelles, etc; États-Unis -- Histoire -- 1754-1763 (Guerre de Sept Ans) -- Romans, nouvelles, etc; FICTION -- Historical; Delaware Indians; Frontier and pioneer life; Iroquois Indians; New York (State); United States; 1754-1763; War stories; War stories; Historical fiction; History; Fiction; War stories; Historical fiction; Historical fiction